Auslandsvermögen und Kapitalertragsbilanz der Bundesrepublik - Otmar Issing (Kredit und Kapital, 1971)
Foreign Assets and Balance of Investment Income of the Federal Republic of Germany The article begins with a surprising statement: Since 1950, the Federal Republic has had a growing surplus of foreign investments over foreign liabilities; but in the same period, up to 1965, the balance of investment income has deteriorated more and more. In comparison, over the same length of time the United States have recorded a mostly parallel development of net foreign investment and the balance of investment income. There is a variety of reasons for this unusual trend in the German balance of payments: 1. There are several defects in the balance-of-payments statistics which result in exaggeration of the deficit on the balance of investment income. 2. After the war, Germany lost her entire foreign assets, while the foreign capital in Germany was still in existence at the end of World War II. 3. Payments by Germany under the London Convention of 1953 reduced interest payments only to a slight extent. 4. The most important item is the foreign investments of the German Bundesbank, which make a high percentage of total foreign investment since 1950. 5. Germany was mainly a net-debtor of long-term private capital, and a netcreditor of capital only to the extent of the transactions of the central government. Germany's adverse position is shown by the comparison with the U.S. A. 6. The same unfavourable development can be observed ın the case of direct investments. 7. The long-term trend was influenced above all by the undervaluation of the Deutsche Mark by the official exchange rate. 8. The appendix contains several computations of the low investment income from official foreign exchange reserves.
Keywords: 330